Pain and Sleep Around Hysterectomy: A Prospective Cohort Study [15D]. (May 2017) - Levy, Melanie; Meers, Jessica; Stout-Aguilar, Jacqueline; Kilic, Gokhan; Borahay, Mostafa; Nowakowski, Sara
Abstract : INTRODUCTION: Hysterectomy is the most frequent non-pregnancy-related major surgery in reproductive-aged women. Proper pain management represents a critical peri-operative goal. Although the association of chronic pain and sleep disorders is well known, the relation between perioperative pain and sleep is less studied. This study tested the hypothesis pre-operative sleep pattern would predict post-hysterectomy pain perception. METHODS: A prospective cohort study of women undergoing hysterectomy for benign conditions. Institutional Review Board approval obtained. Measures included: PROMIS-PI 3a (pain intensity), total sleep time measured by wrist actigraphy and daily sleep diary, and time awake after sleep onset measured by actigraphy and sleep diary. Sleep diary and actigraphy sleep variables were averaged over 7 nights preceding and 7 nights following hysterectomy. RESULTS: Sixteen women (41±7.3 years old) participated in the study. Repeated measures ANOVA revealed a significant increase from pre- to post-hysterectomy in actigraphy total sleep time (402±43.7 vs. 481±85.8 min, p=.023), and diary time awake after sleep onset (28±11.4 vs. 58±17.7 min, p=.014). Pre-hysterectomy diary total sleep time was negatively correlated with post-hysterectomy pain intensity (r=-.92, p=.01). Pre-hysterectomy actigraphy time awake after sleep onset was positively correlated with post-hysterectomy pain intensity (r=.86, p=.008). CONCLUSION: Findings indicated that sleep duration and disturbance increased following hysterectomy. Shorter sleep duration and more disturbed sleep before hysterectomy were associated with greater perceived pain intensity following hysterectomy. These findings suggest that pre-operative sleep interventions could improve pain perception and recovery following hysterectomy.